Infective Exacerbation of Pasteurella multocida - Mayumi Hamada; Noha Elshimy; Hatem Abusriwil (Case Reports in Infectious Diseases)
An 89-year-old lady presented with a one-day history of shortness of breath as well as a cough productive of brown sputum. Her medical history was significant for chronic obstructive pulmonary disease (COPD). She was in severe type one respiratory failure and blood tests revealed markedly raised inflammatory markers; however her chest X-ray was clear. On examination there was bronchial breathing with widespread crepitations and wheeze. She was treated as per an infective exacerbation of COPD. Subsequent blood cultures grew Pasteurella multocida, a common commensal in the oropharynx of domesticated animals. The patient was then asked about any contact with animals, after which she revealed she had a dog and was bitten on her left hand the day before admission. We should not forget to enquire about recent history of injuries or animal bites when patients present acutely unwell. She made a complete recovery after treatment with penicillin.